Natural Dyes from Roselle Flower as a Sensitizer in Dye-Sensitized Solar Cell (DSSC) - Dayang Suriani; Muhammad Irwanto Misrun; Gomesh Nair; Baharuddin Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Hibiscus Sabdariffa L. well known as Roselle flower was used as sensitizers for Dye-Sensitized Solar Cell (DSSC). The dyes were extracted using distilled water (DI) and ethanol (E) extract solvent in an ultrasonic cleaner for 30 minutes with a frequency of 37 Hz by using ‘degas’ mode at the temperature of 30°. Doctor blade method was applied in the fabrication of titanium dioxide (TiO2) on ITO glass. Absorption spectra of Roselle dye with different extract solvent were tested using Evolution 201 UV-Vis Spectrophotometer. Fourier-Transform Infrared (FTIR) was used to identify the functional active group in extract dye. Based on FTIR result, the broad absorption at peak 2889 cm-1, 2976 cm-1, and 3366 cm-1 attributed to the O-H stretching which is the presence of hydroxyl group. The use Field Emission Scanning Electron Microscopy (FESEM) and Energy-Dispersive Spectroscopy (EDS) analysis are to characterize the surface morphology and element in the TiO2 thin film.